The possibility of using gastroenteroprotector rebamipide to improve the antithrombotic therapy safety - Natalya M. Vorobyeva; Irina P. Malaya; Vadim D. Zakiev; Olga N. Tkacheva (LLC "MEDIAFORMAT", 2023)
Antithrombotic drugs (antiplatelet agents and anticoagulants) are widely used in cardiological practice for primary and secondary prevention of thrombotic/thromboembolic complications, however, the use of such drugs is associated with the increased risk of hemorrhagic complications, including gastrointestinal hemorrhage. Assessment by video capsule endoscopy has shown that the damaging effects of antithrombotic drugs are not confined to the upper gastrointestinal mucosa, but also expand to the lower gastrointestinal tract, affecting small and large intestine. That is why it is reasonable to use rebamipide, the unique drug combining gastroprotective and enteroprotective effects, to protect gastrointestinal mucosa and prevent gastrointestinal hemorrhage. The drug exerts its effects at all three structural levels of the mucous membrane throughout the gastrointestinal tract; its efficacy and safety have been confirmed by multiple randomized clinical trials.